Representation of Mizan In Lamongan Folklore: An Islamic Ecotheological Perspective of Seyyed Hossein Nasr - Niswatin Solihah; Abdul Karim Wirawan (Universitas Airlangga, 2026)
The increasingly complex ecological crisis reflects a disharmonious relationship between humans and nature. This study aims to describe the representation of ecotheology in Lamongan folktales through the concepts of mizan (ecological balance), ihya’ al-mawat (land revitalization), and fasad fil-ardh (the prohibition of environmental destruction). The study employs an ecocritical approach with a qualitative descriptive method. The data consist of excerpts from interview transcripts with narrators of Lamongan folktales. The findings reveal that ecotheological values are represented through ecological balance, land rehabilitation and reforestation, and the prohibition of ecological and socio-ecological destruction. These findings indicate that Lamongan folktales contain environmental ethics grounded in spiritual, cultural, and religious values, making them a potential medium for local wisdom-based ecological education.